Identifying Key issues in Digital Transformation of SMEs: A Study of Data from 2017-2022 in the European Union - Barbara SIUTA-TOKARSKA; Magdalena BELNIAK (Communications of International Proceedings, 2025)
The growing pace of digital transformation is reshaping business structures across the European Union. While large enterprises have embraced mainly digital technologies, small and medium-sized enterprises (SMEs) remain unevenly integrated into the digital economy. This paper investigates the extent and nature of digital transformation among SMEs in the EU between 2017 and 2022. The study is motivated by the observed gap in the literature, where quantitative analyses often focus on large firms, overlooking the micro-level dynamics of SME digitalization. Using an indicator-based approach grounded in Eurostat and DESI data, the research evaluates key metrics of digital adoption, including internet access, e-commerce activity, and the use of advanced technologies such as cloud computing and artificial intelligence. The methodology combines descriptive and comparative analysis to identify trends and disparities in digital maturity across EU member states. The findings reveal that although SMEs have made incremental progress in digital transformation, significant structural barriers persist, particularly related to financing, skills, and access to ICT infrastructure. The results underline the need for targeted policy interventions to enhance SMEs’ participation in the digital economy and to promote inclusive technological growth within the EU.
Keywords: Digitalization; SMEs; European Union; Technological Innovation Policy; Indicator-based Analysis